Comparative Analysis of Gut Microbiota Diversity Across Different Digestive Tract Sites in Ningxiang Pigs - Wangchang Li; Xianglin Zeng; Lu Wang; Lanmei Yin; Qiye Wang; Huansheng Yang (Animals)
Background: Microbial communities in the gastrointestinal tract play a critical role in nutrient absorption, metabolism, and overall health of animals. Understanding the structure and function of tissue-specific microbial communities in Ningxiang pigs is essential for optimizing their growth, development, and nutritional efficiency. However, the diversity and functional roles of microbiota in different nutrient absorption tissues remain underexplored. Methods: We collected samples from four key nutrient absorption tissues (NFC: Cecal Content, NFI: Ileal Content, NFL: Colonic Content, NFG: Gastric Content, N = 6) of Ningxiang pigs and performed 16S rRNA gene sequencing to analyze microbial community composition. Bioinformatics analyses included alpha and beta diversity assessments, linear discriminant analysis effect size (LEfSe) for biomarker identification, and PICRUSt2-based functional prediction. Comparative metabolic abundance analysis was conducted to explore functional differences among tissues. Results: Alpha diversity indices (ACE, Chao1, Simpson, and Shannon) revealed significant differences in microbial richness and evenness among the four tissues. At the phylum level, Firmicutes dominated the microbiota, while Bacteroidota was prominent in NFC and NFL. LEfSe analysis identified tissue-specific dominant microbial groups, such as f_Prevotellaceae in NFC, o_Lactobacillales in NFG, f_Clostridiaceae in NFI, and f_Muribaculaceae in NFL. Functional profiling using PICRUSt2 showed that the microbiota was primarily involved in organismal systems (e.g., aging, digestion), cellular processes (e.g., cell growth, transport), environmental information processing (e.g., signaling), genetic information processing (e.g., transcription, translation), and metabolic regulation (e.g., amino acid and carbohydrate metabolism). Comparative metabolic abundance analysis highlighted distinct functional profiles across tissues, with significant differences observed in pathways related to the immune system, energy metabolism, lipid metabolism, transcriptional and translational regulation, and aging. Conclusions: Our findings demonstrate that tissue-specific microbial communities in Ningxiang pigs exhibit distinct structural and functional characteristics, which are closely associated with nutrient absorption and metabolic regulation. These results provide valuable insights into the roles of microbiota in the growth and health of Ningxiang pigs and pave the way for future studies on microbe-mediated nutritional interventions.